Family Cohesion and Adolescent Psychological Well-being: Evidence from Senior High Schools in Ghana - Augustina Atkinson Dadebo; Emmanuel Eshun; Bernice Serwaa Ofosuhene Peasah; Abigail Dzama Anderson; Theresa Dede Lawer (Archives of Current Research International, 2025)
This study examined the relationship between family cohesion and adolescents’ psychological wellbeing using a survey research design. Simple random sampling technique was used to select 326 respondents from West Africa Senior High School and Presbyterian Boys Senior High School, Legon in the La-Nkwantanag Municipality, Accra. Data was collected using self-report questionnaires which consist of the Ryff’s Psychological Wellbeing Scale and the Family Adaptability and Cohesion Evaluation Scale (FACES IV). Findings showed that a significant positive correlation exist between family cohesion and psychological wellbeing among students. Male students also reported significantly higher levels of family cohesion than female students. Result also showed that students whose parents are married have the highest level or quality of family cohesion, followed by those whose parents are separated, divorced and widowed respectively. Results finally revealed that students who live with their parents have significantly higher levels or quality of family cohesion than those who do not live with their parents. It is therefore concluded that a significant positive correlation exists between family cohesion and psychological wellbeing among students. This therefore suggests that an increase in level or quality of family cohesion leads to an increase in psychological wellbeing of adolescents in the La-Nkwantanang Municipality in Accra.